Protection of People at Sea under International Law: Lesson Learnt from Pushback Action to boat people in Indonesia and Malaysia - Puspitawati, Dhiana; Susanto, Fransiska Ayulistya (Faculty of Law, Universitas Brawijaya, 2023)
People at sea, one of which is the Boat People, has become a problem not only for Europeans but also in Southeast Asia with increasing asylum seekers from Rohingya and migrants from Bangladesh. Southeast Asia is already facing the problem of boat people returning from the Vietnam Asylum. However, an old story becomes a new story that never ends in Southeast Asia when the strategist state to Sanctuary did not participate in the 1951 Geneva Convention. As a result, many people faced pushback and died or lost at sea. This research will discuss the extent to which “protection of persons at sea” and the “search and rescue” can cover the protection of boat people under UNCLOS 1982. This study also analyses how UNCLOS 1982 will work to protect boat people when states protect themselves with the